2002
DOI: 10.1038/sj.leu.2402655
|View full text |Cite
|
Sign up to set email alerts
|

Role of the E45K-reduced folate carrier gene mutation in methotrexate resistance in human leukemia cells

Abstract: Collectively, the results demonstrate that expression of E45K hRFC leads to increased MTX resistance due to decreased membrane transport and, secondarily, from alterations in binding affinities and transport of folate substrates. However, despite these findings, we could find no evidence of this mutation in 121 childhood ALL samples, suggesting that it does not contribute to clinical MTX resistance in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The first report of SLC-mediated transport of anticancer drugs dealt with the antifolate drug methotrexate, which is transported by members of the SLC19A family (SLC19A1-3) (Goldman and Matherly, 1985). Decrease or loss of SLC19A1 gene expression has been detected in cancer cell lines made resistant to antifolates in vitro (Gifford et al, 2002). We observed that SLC19A1 was down-regulated only in H727 cells compared with lung tissues; it was overexpressed in 16HBE, 1HAE0, A549, and Calu-1 cells.…”
Section: Number Of Genes Differentially Expressed Between Lung Cell Mmentioning
confidence: 55%
“…The first report of SLC-mediated transport of anticancer drugs dealt with the antifolate drug methotrexate, which is transported by members of the SLC19A family (SLC19A1-3) (Goldman and Matherly, 1985). Decrease or loss of SLC19A1 gene expression has been detected in cancer cell lines made resistant to antifolates in vitro (Gifford et al, 2002). We observed that SLC19A1 was down-regulated only in H727 cells compared with lung tissues; it was overexpressed in 16HBE, 1HAE0, A549, and Calu-1 cells.…”
Section: Number Of Genes Differentially Expressed Between Lung Cell Mmentioning
confidence: 55%
“…2). The identical Glu45Lys mutation to that originally reported in MTX resistant murine cells [95] was identified in separate CCRF-CEM human T-cell ALL isolates [99,107]. It is interesting that loss of MTX uptake and resistance in Glu45Lys mutants was accompanied by dramatically increased uptake of reduced folates and folic acid, resulting in elevated pools of cellular folates [95,99].…”
Section: Molecular Mechanisms Of Rfc-mediated Resistancementioning
confidence: 96%
“…Several human CEM-CCRF MTXresistant cell lines, generated in different laboratories, with decreased MTX influx V max , were subsequently shown to have a Glu45Lys mutation in the first TMD (Jansen et al, 1998;Drori et al, 2000), the latter homologous to a mutation identified in murine leukemia cells selected for MTX resistance under chemical mutagenesis . However, this mutation has not been detected in cells obtained directly from patients with leukemia (Whetstine et al, 2001;Gifford et al, 2002). The intrinsic resistance of sarcoma 180 cells to MTX as compared to L1210 leukemia cells was associated with a single amino-acid difference at codon 297 (Asn in the latter, Ser in the former) resulting in an increase in the influx K t without a change in V max (Roy et al, 1998).…”
Section: Resistance Associated With Impaired Rfc-mediated Transportmentioning
confidence: 99%
“…However, to date, no mutations in RFC have been identified in lymphoblasts obtained from patients. In particular, a search for the Glu45Lys mutation within the first TMD of RFC, detected frequently in a variety of preclinical studies, was not identified in clinical specimens (Whetstine et al, 2001;Gifford et al, 2002).…”
Section: Novel Gene Therapy Approaches That Exploit Mutations In Targmentioning
confidence: 99%